PENGARUH KEMAMPULABAAN DALAM MEMEDIASI KINERJA KEUANGAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFACTURE SECTOR MINING AND MINING SERVICE YANG GO-PUBLIC DI INDONESIA - LCA Robin Jonathan (LPPM University 17 Agustus 1945 Samarinda, 2017)
This study aims to determine and analyze the effect of profitability in mediating the financial performance projected in the ratios of efficiency, liquidity and leverage to the value of the company making sectormining and mining services go-public in IndonesiaThe development of manufacture sector mining and mining service has reached 40 companies and from that number is taken the financial statements of the period 2013-2015, in the analysis by using regression analysis of mediation variables with Productof Coefficient method developed by Sobel. Sobel test results states that profitability has a significant effect in mediating leverage to corporate value and no significant effect in mediating the variables of efficiency and liquidity to the value of the company.